Revisiting the Invisible Hiding Place - Jasper Coppes (Footprint)
This paper explores different perspectives on the concept of place. It deals with questions that arose from this subject during my practice as a visual art student at the Gerrit Rietveld Academy. Accordingly this text can be read as a theoretical and literary inquiry, investigating those questions which I see myself confronted with in my artistic practice. It starts with an attempt to clarify ideas that have been formed by thought and theory until now about the content of this subject. Subsequently it has been my intention to introduce ideas about the impossibility and the desire of inhabiting an empty place, ideas about the role of invisibility and absence. For maybe the empty place resists any attempt to understand it, even the conception of it being a place, and becomes a dimension of absence.